Exploring Culinary Films as a Form of Health Literacy: A Case Study of Aruna dan Lidahnya in Indonesia - Adiprabowo, Vani Dias; Sanofi, Zuhairi (Universitas Ahmad Dahlan, 2023)
The lack of Indonesian culinary-themed films that discuss public health literacy is reflected in the limited number of titles available. The film, Aruna dan Lidahnya, is a topic of discussion as it raises issues related to culinary tourism, religion, public policy, and public health literacy, specifically the avian influenza virus outbreak, which has objective and subjective dimensions. This study aims to discover how culinary films are constructed in health literacy and why the film is constructed as a form of health literacy. This qualitative study uses a case study approach to investigate how and why culinary films are constructed as a form of health literacy, specifically focusing on the film Aruna dan Lidahnya. The researchers used primary and secondary data from the film from literature studies and observations and applied data analysis techniques to interpret the data. The film Aruna dan Lidahnya promotes the potential of local cuisine as a unique attraction to grow the economy of tourist destinations. It also emphasizes the importance of health communication in raising public awareness about the avian influenza virus and following health protocols. The film highlights the need for cultural and local wisdom-based tourism development for a more ethical and aesthetic tourist attraction. Aruna dan Lidahnya is a film that highlights the potential of local cuisine in developing tourist destinations in four cities affected by the avian influenza virus. Developing tourist destinations based on local cuisine can improve social welfare and the area's economy and be a unique attraction for cultural tourism. The film also emphasizes the importance of health communication, following health protocols, and spreading awareness about the avian influenza virus in the context of local culinary opportunities.